(untitled) (International Conference on Computers in Education, 2022)
Digital storytelling (DST), an innovative pedagogical approach, has the potential to facilitate active learning in the classroom. Literature indicates that engagement is essential to effective learning. However, the investigation of the impacts of DST on learning engagement in English as a Foreign Language (EFL) education in China is scarce, especially in the K-12 context. Moreover, although related efforts have been made, few studies examine these effects with a clear focus on classroom engagement. To address this issue, this study adopted a 5-factor classroom engagement framework (affective engagement, behavioral engagement-compliance, behavioral engagement-effortful class participation, cognitive engagement, and disengagement) to investigate whether learning with DST affects multidimensional classroom engagement in a Grade 6 English class. A quasi-experimental approach with pretest and posttest was conducted, and data were collected from 70 Grade 6 students via Classroom Engagement Inventory. The quantitative results using ANCOVA revealed that there was a significant difference in overall classroom engagement between the experimental (n=35) and control groups (n=35) in the posttest, particularly in terms of the behavioral engagement-compliance and cognitive engagement. In other words, it was found that, when learning with DST in English class, students were more likely to adhere to the class norms and arrangements, as well as devote mental efforts to be strategic and self-regulated. Yet, no significant difference was manifested in affective engagement and behavioral engagement-effortful class participation, suggesting that the use of DST may not bring about more positive emotions and effortful involvement in English class. This study contributes to a realistic perspective for EFL educators and teachers to understand the potential of the DST approach through the lens of classroom engagement. The second stage of this project has been exploring the reason behind the research results, shedding light on possible mediators within DST that could facilitate or impair certain aspect(s) of classroom engagement. Further implications for DST integration in the EFL classroom can be proposed.